Respiratory muscle function and exercise limitation in patients with chronic obstructive pulmonary disease: a review. (2nd January 2018) - Charususin, Noppawan; Dacha, Sauwaluk; Gosselink, Rik; Decramer, Marc; Von Leupoldt, Andreas; Reijnders, Thomas; Louvaris, Zafeiris; Langer, Daniel
ABSTRACT: Introduction : Respiratory muscle dysfunction is common and contributes to dyspnea and exercise limitation in patients with chronic obstructive pulmonary disease (COPD). Improving dynamic function of respiratory muscles during exercise might help to reduce symptoms and improve exercise capacity. Areas covered : The aims of this review are to 1) summarize physiological mechanisms linking respiratory muscle dysfunction to dyspnea and exercise limitation; 2) provide an overview of available therapeutic approaches to better maintain load-capacity balance of respiratory muscles during exercise; and 3) to summarize current knowledge on potential mechanisms explaining effects of interventions aimed at optimizing dynamic respiratory muscle function with a special focus on inspiratory muscle training. Expert commentary : Several mechanisms which are potentially linking improvements in dynamic respiratory muscle function to symptomatic and functional benefits have not been studied so far in COPD patients. Examples of underexplored areas include the study of neural processes related to the relief of acute dyspnea and the competition between respiratory and peripheral muscles for limited energy supplies during exercise. Novel methodologies are available to non-invasively study these mechanisms. Better insights into the consequences of dynamic respiratory muscle dysfunction will hopefully contribute to further refine and individualize therapeutic approaches in patients with COPD.